Challenges in the diagnosis and management of sleeping sickness in Tanzania: a case report - Sindato, C; Kibona, SN; Nkya, GM; Mbilu, TJ; Manga, C; Kaboya, JS; Rawille, F (Tanzania Journal of Health Research, 2008)
In Tanzania sleeping sickness presents a serious threat to human health with a country-wide average of 400 cases reported annually. Both wild and domestic animals have been found to play a significant role in the epidemiology of sleeping sickness. Serengeti National Park in northern Tanzania, has experienced a number of sleeping sickness epidemics since 1922. The epidemics were associated with abundant game animals in the areas and Glossina swynnertoni was incriminated as the main vector. However since 2001 there has been no case of sleeping sickness reported from the park. This case report highlights on the possibility of resurgence and challenges in the diagnosis and management of sleeping sickness in Serengeti. A 38 years old Tanzanian man working in the Serengeti National Park who had experienced various tsetse bites was presented with a febrile condition and history of unsuccessful case management at different health facilities. Blood and cerebrospinal fluid (CSF) samples were examined for the presence of trypanosomes using wet film, Field\'s stain and concentration techniques. Typanosoma brucei rhodesiense were detected in both the blood and CSF samples. The patient was treated successfully with melarsoprol. The results of this case study highlight the possibility of resurgence of sleeping sickness in the park hence calls for the need to create more awareness among the community and clinicians. There is need for early reporting to health facility and strengthening the diagnostic capacity of healthcare facilities in and around national parks endemic for sleeping sickness. Keywords: Diagnosis, treatment, sleeping sickness, trypanosomiasis, Tanzania Tanzania Journal of Health Research Vol. 10 (3) 2008: pp. 177-181